Moral Hazard in the principal-agent problem - Zatlukal, Marek; Hořejší, Bronislava, 1955-; Macáková, Libuše, 1955-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
This paper will introduce the reader to the issues of moral hazard in a principal-agent setting, with the primary focus on the incentive pay models of moral hazard. Firstly, with an introduction and analysis of various microeconomic models designed to alleviate the problems of moral hazard, and secondly, with an analyses of these models in the context of a specific company, the aim of this thesis is to offer a comprehensive understanding of the specific problems caused by moral hazard in the principal-agent problem, as well as the mechanisms used to lessen such problems in the real business environment and their connection to the theoretical microeconomic models.
Vedoucí práce: Bronislava Hořejší
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses